Outcome of rheumatic heart disease with history of sydenham chorea: a case report - Sondang Hazewinkel Suringa Siagian; Agung Triono; Sasmito Nugroho (Indonesian Pediatric Society, 2026)
Rheumatic heart disease (RHD) is an important health problem in adolescents and is associated with a decreased quality of life due to impaired physical and emotional functioning. Poor physical condition is often related to recurrent episodes of acute rheumatic fever (ARF), which contribute to the progression of RHD. Children with history of Sydenham chorea have a recurrence rate of 20% within months after the first episode, and could present without any other ARF symptoms.